G Protein Coupled Receptors Potentially Involved in Oligodendrogenesis: A Gene Expression Analysis - Neda Karami; Hadi Aligholi; Moosa Rahimi; Hassan Azari; Tahereh kalantari (Tehran University of Medical Sciences, 2022)
Background: Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system characterized by infiltration of inflammatory leukocytes to the CNS followed by oligodendrocyte cell death, myelin sheath destruction, and axonal injury. A logical incidence occurring after demyelination is remyelination. G-protein coupled receptors (GPCRs) activate internal signal transduction cascades through binding to different ligands. This family of receptors are targeted by more than 40% of currently marketed drugs. GPCRs can be successfully targeted for induction of remyelination. GPCRs highly enriched in oligodendrocyte progenitor cells compared to oligodendrocytes are proposed to hamper oligodendrocyte differentiation and therefore their inhibition might induce remyelination. This study aimed to investigate the expression of GPCRs in silico and in vitro. Methods: We performed gene expression analysis using DAVID and Panther websites on a RNA-seq dataset (GSE52564 accession number). Primary embryonic neural stem/progenitor cell isolation and culture were performed and subsequently NSPCs were characterized by Immunocytochemistry with Anti-Nestin antibody. Expression of GPR37L1, EDNRB, PDGFRα, CNPase and GFAP were assessed using real-time PCR. All the experiments were conducted at Shiraz University of Medical Sciences (SUMS), Shiraz, Iran, in the year 2018. Results: The 14 most highly expressed GPCRs in oligodendrocyte progenitor cells (OPCs) compared to Oligodendrocytes were presented in our study. Conclusion: The investigation of the most highly expressed GPCRs in OPCs compared to oligodendrocyte in silico and in vitro presents the significant role of GPCRs in remyelination induction. Among the 14 GPCRs mentioned in this study, GPR37L1 is a potential remyelinating drug target and is suggested for further studies.